2018
DOI: 10.1515/cclm-2018-0596
|View full text |Cite
|
Sign up to set email alerts
|

Preanalytical stability of [-2]proPSA in whole blood stored at room temperature before separation of serum and plasma: implications to Phi determination

Abstract: Background [-2]proPSA seems to outperform free/total prostate-specific antigen (PSA) ratio in prostate cancer diagnosis. However, [-2]proPSA stability remains an underestimated issue. We examined [-2]proPSA stability over time in whole blood before separation of serum and plasma and its implications for prostate health index (Phi) determination. Total PSA (tPSA) and free PSA (fPSA) stabilities were also assessed. Methods Blood was drawn from 26 patients and separated in two tubes for plasma (K2EDTA and K2EDTA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
2
4
0
Order By: Relevance
“…The enzyme ALP showed minimal changes in this study, with reliable results obtained at every analysis within 24 hours of the sample collection. This was consistent with the findings by Dittadi et al (2019) who determined a minor increase of ALP activities in serum samples from its baseline values during the first 8 hours of storage. The observed changes however were within acceptable limits, as shown by the mean percentage difference that consistently remained below the calculated RCV.…”
Section: Concentration Changes and The Stability Of The Selected Bioc...supporting
confidence: 93%
“…The enzyme ALP showed minimal changes in this study, with reliable results obtained at every analysis within 24 hours of the sample collection. This was consistent with the findings by Dittadi et al (2019) who determined a minor increase of ALP activities in serum samples from its baseline values during the first 8 hours of storage. The observed changes however were within acceptable limits, as shown by the mean percentage difference that consistently remained below the calculated RCV.…”
Section: Concentration Changes and The Stability Of The Selected Bioc...supporting
confidence: 93%
“…On the other hand, serum samples might suffer from similar limitations depending on blood sampling and processing procedures. Such preanalytical factors have been shown to influence the quantification of analytes in clinical chemistry as well as in immunoassays, for example for the quantification of free PSA [26,38,39]. Our results show that serum levels of THBS1 and CTSD are largely unaffected by pre-analytical factors, with measured concentrations relative to reference conditions between 80% and 120%.…”
Section: Plos Onementioning
confidence: 65%
“…In whole blood at room temperature, a median phi increase not higher than 15% in the first 3 h has been reported [61]. Interestingly, in a recent study, Dittadi et al [62] demonstrated that [-2]proPSA was more stable in plasma EDTA compared to serum. However, due to the limited number of cases examined in this study (n = 26), it is not still possible to assess whether the use of plasma EDTA improved phi clinical performance.…”
Section: Limitationsmentioning
confidence: 93%